Level Up Students' Career Planning through Maze Simulation-Based Group Guidance - Mufliha, Faizatul; Yuliana, Anis Tri; Mafruhah (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2026)
This study aims to analyze in depth the effectiveness of group guidance services based on a maze simulation game in optimizing the career planning of students at MTs Nurul Iman Pagarbatu. The study used a quasi-experimental method with a One Group Pretest–Posttest design. The study subjects were 8 eighth-grade students selected through purposive sampling technique based on their low career planning scores. The study instrument used a Likert-shaped career planning scale that has been tested for validity and reliability. Treatment was given through four group guidance service sessions integrated with the maze simulation game. Data analysis was conducted using a Paired Sample t-Test. The results of the study clearly showed an increase in the average career planning score. The results of the hypothesis test showed a significant difference between the pretest and posttest. Thus, it can be firmly concluded that group guidance services based on the maze simulation game are effective in optimizing students' career planning.